HEMIEPIPHYSIODESIS USING EIGHT-PLATE VERSUS BLOUNT STAPLE TO CORRECT GENU VALGUM AND GENU VARUM - Majewski Rodrigues, Natasha Vogel; Guarniero, Roberto; Fortes Villas Boas, Paulo Jose [UNESP]; Miranda, Bruno Rodrigues de; Montenegro, Nei Botter (Atha Comunicacao & Editora, 2020)
Objective: Our objective is to evaluate whether the use of guided growth with eight-plates is more effective than the use of Blount staples for the correction of the idiopathic genu varum or idiopathic genu valgum. Methods: A systematic review (SR) was carried out according to the appropriate methodology for randomized clinical trials (RCTs). We searched seven databases through a previously defined methodology, and we included RCTs, regardless of language, period of publication and status of publication. Results:Resulted in 6830 articles retrieved. Of theses, we identified 14 potential eligible studies. but just one RCT was included for the SR. The included RCT compares the eight-plate and the Blount staple and showed no statistically significant difference for the outcomes of time to correct the deformity, postoperative pain after 24 hours and postoperative pain after 72 hours. The study is of low or very low level of evidence to determine the most effective technique. We didn't find a RCT that compared the correction of the genu varum..Conclusion: Good quality randomized clinical trials comparing Blount staples versus eight-plaque must be performed to determine which technique is superior for coronal plane corrections.
Keywords: Child; Adolescent; Genu Varum; Genu Valgum